METODE PENYELIDIKAN DALAM PSIKOLOGI PERKEMBANGAN (IAI Sunan Giri Trenggalek, 2025)
Psychology is the science that studies the human psyche and its development. In this article, we discuss common research methods in developmental psychology, including experiments, tests, clinical methods, observation, and case studies. Each method has strengths and weaknesses that need to be considered. This research uses the library research method by examining various reference books and relevant prior research findings to obtain a theoretical foundation and strengthen the analysis of the issues studied. This method was chosen because the research focuses on the conceptual review of investigative methods in developmental psychology, thus not requiring field data collection. It is concluded that the selection of an appropriate method plays a crucial role in producing valid and reliable findings. Every research design has strengths and limitations that need to be considered in accordance with the research objective and the characteristics of the subjects being studied. Conceptually, a deep understanding of research method principles allows researchers to design studies capable of accurately capturing individual developmental changes and differences between groups. The mastery of research methods is not merely procedural but is also an important conceptual foundation for the scientific understanding of human development and the application of effective interventions in the context of psychology, education, and clinical practice.